2013
DOI: 10.1002/cncr.27956
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐reported outcomes after 3‐dimensional conformal, intensity‐modulated, or proton beam radiotherapy for localized prostate cancer

Abstract: BACKGROUND-Recent studies have suggested differing toxicity patterns for patients with prostate cancer who receive treatment with 3-dimensional conformal radiotherapy (3DCRT), intensity-modulated radiotherapy (IMRT), or proton beam therapy (PBT).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
61
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 46 publications
6
61
1
Order By: Relevance
“…Prospectively collected quality-of-life scores during the first 2 years were similar in 1243 men after pbt and 204 men after imrt 77 . Gray et al 78 reported that pbt, conformal photon rt, and imrt all result in similar clinically meaningful reductions in bowel (but not urinary) quality-of-life scores at 24 months.…”
Section: Prostatementioning
confidence: 98%
“…Prospectively collected quality-of-life scores during the first 2 years were similar in 1243 men after pbt and 204 men after imrt 77 . Gray et al 78 reported that pbt, conformal photon rt, and imrt all result in similar clinically meaningful reductions in bowel (but not urinary) quality-of-life scores at 24 months.…”
Section: Prostatementioning
confidence: 98%
“…The bowel QOL score is at its lowest 1 or 2 months after treatment, but improves slowly thereafter to near baseline by 1-2 years after treatment [3][4][5]. In our series, most moderate to big problems were seen at 1 month post-SBRT with approximately 10% of patients reporting moderate to big problems with bowel urgency and/or frequency ( Figure 4).…”
Section: Discussionmentioning
confidence: 54%
“…Proctitis following prostate cancer radiotherapy is a critical quality of life issue [1][2][3][4] and the principle doselimiting toxicity [14][15][16]. Currently, there is limited data on proctitis following SBRT for prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proton therapy provides an advantage over IMRT by reducing the radiation dose delivered to normal tissues outside of the target volume 4, 5. Image‐guided treatment delivery, as well as use of endorectal balloons (ERB), have been historically employed to allow for tighter planning target margins thus decreasing the volume of rectum exposed to high radiation doses 6, 7, 8, 9.…”
Section: Introductionmentioning
confidence: 99%